2021
DOI: 10.1111/jcmm.16277
|View full text |Cite
|
Sign up to set email alerts
|

EXT1 methylation promotes proliferation and migration and predicts the clinical outcome of non‐small cell lung carcinoma via WNT signalling pathway

Abstract: DNA methylation is important for lung cancer prognosis. In this work, it is aimed to seek novel biomarkers with DNA methylation‐expression‐pathway pattern and explore its underlying mechanism. Prognostic DNA methylation sites and mRNAs were screened in NSCLC data set from TCGA, and further validated using the samples retrospectively collected, and EXT1 was identified as a potential target. Gene body methylation of three CpG sites (cg03276982, cg11592677, cg16286281) on EXT1 was significantly associated with cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…Therefore, we speculated that circβ-catenin-370aa, a novel peptide, circβ-catenin re- it is known that β-catenin can increase the malignant phenotype of NSCLC. 41,42,56 In summary, these results indicated that circβ-catenin encoded β-catenin-370aa to combine with GSK3β, leading to escape the degradation of β-catenin induced by GSK3β.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Therefore, we speculated that circβ-catenin-370aa, a novel peptide, circβ-catenin re- it is known that β-catenin can increase the malignant phenotype of NSCLC. 41,42,56 In summary, these results indicated that circβ-catenin encoded β-catenin-370aa to combine with GSK3β, leading to escape the degradation of β-catenin induced by GSK3β.…”
Section: Discussionmentioning
confidence: 78%
“…co‐IP results confirmed that circβ‐catenin knockdown or overexpression was able to enhance or reduce the combination between GSK3β and β‐catenin. In addition, it is known that β‐catenin can increase the malignant phenotype of NSCLC 41,42,56 …”
Section: Discussionmentioning
confidence: 99%
“…And EXT1 may affect tumor survival by activating the Wnt signaling pathway By PPI network analysis, we found that EXT1 was associated with KIF2C. EXT1 may affect tumor survival by activating the Wnt signaling pathway ( Kong et al, 2021 ), and it has also been demonstrated that KIF2C is activated by the Wnt signaling pathway and thus can promote liver cancer progression by activating mTORC1 signaling ( Wei et al, 2020 ), so we speculate that EXT1 may influence KIF2C and thus promote tumor development.…”
Section: Discussionmentioning
confidence: 90%
“…Figure 11 shows that KIF2C interacts with genes such as CENPH, ADAM9, NDEL1, and EXT1 and is associated with biological functions such as tubulin binding, sister chromatid segregation, and MHC II antigen presentation, suggesting that KIF2C is involved in cell cycle and immune regulation. In addition, previous studies found that the KIF2C-related CENPH, EXT1, can promote tumor progression (Wu et al, 2015; Lu et al, 2017; Kong et al, 2021 ) and ADAM9 has a significant role in tumor growth, metastasis, and immune evasion (Chou et al, 2020).…”
Section: Resultsmentioning
confidence: 98%
“…EXT1 is an endoplasmic reticulum-resident type II transmembrane glycosyltransferase involved in the chain elongation step of heparan sulfate biosynthesis. Diseases associated with EXT1 include hereditary multiple exostoses, non-small cell lung carcinoma and Chondrosarcoma [32][33][34].…”
Section: Discussionmentioning
confidence: 99%